Systematic Literature Review: Pemanfaatan Software Matematika untuk Pembelajaran dengan GeoGebra - Cyntia Suarni Arifin; Yahfizham Yahfizham (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
In the world of education today, computers have an important role as a learning medium for efficient learning. The GeoGebra application is an application used to visualize mathematical objects quickly, accurately and effectively so that it can shorten the time in solving mathematical problems. This research uses a literature study type of research by identifying and evaluating the results of previous research. In this research, 5 previous journals were identified. From the results of this research, it was found that the use of GeoGebra in learning was quite good. This is because GeoGebra has a positive influence that can support the learning carried out.